2021
DOI: 10.1111/1471-0528.16974
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and vertical transmission: assessing the expression of ACE2/TMPRSS2 in the human fetus and placenta to assess the risk of SARS‐CoV‐2 infection

Abstract: Background Pregnant women have been identified as a potentially at‐risk group concerning COVID‐19 infection, but little is known regarding the susceptibility of the fetus to infection. Co‐expression of ACE2 and TMPRSS2 has been identified as a prerequisite for infection, and expression across different tissues is known to vary between children and adults. However, the expression of these proteins in the fetus is unknown. Methods We performed a retrospective analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 50 publications
3
23
0
2
Order By: Relevance
“…156 While most studies of COVID-19 in pregnancy focus on severe cases, there is growing evidence suggesting that both mild and severe SARS-CoV-2 infection during pregnancy alters inflammatory responses at the maternal-fetal interface despite the absence of ACE2 and TMPRSS2 expression. 155,159 Single-cell RNA sequencing of placental tissues from pregnant women with severe SARS-CoV-2 infection revealed that most of the DEGs between infected cases and controls belonged to maternal T cells and macrophages with minimal alterations in fetal cells. 157…”
Section: Viral and Bacterial Infectionsmentioning
confidence: 99%
“…156 While most studies of COVID-19 in pregnancy focus on severe cases, there is growing evidence suggesting that both mild and severe SARS-CoV-2 infection during pregnancy alters inflammatory responses at the maternal-fetal interface despite the absence of ACE2 and TMPRSS2 expression. 155,159 Single-cell RNA sequencing of placental tissues from pregnant women with severe SARS-CoV-2 infection revealed that most of the DEGs between infected cases and controls belonged to maternal T cells and macrophages with minimal alterations in fetal cells. 157…”
Section: Viral and Bacterial Infectionsmentioning
confidence: 99%
“…However, there is no increased risk for neonates apart from abnormal ophthalmologic outcomes identified in 15% of cases in a previous study (92). The absence of the co-expression of TMPRSS2 and ACE-2 in the placenta across the second trimester and at term, as well as the absence of ACE2 in the foetal lung help explain the rarity of vertical transmission (93). Fortunately, COVID-19 symptoms in children tend to be milder and slightly different from those in adults (89).…”
Section: Looking Back One Year Later: Developments Since the Workhopmentioning
confidence: 85%
“…Looking back, 14 months after the '6th Workshop on Paediatric Virology', the volume of literature and data on SARS-CoV-2 and COVID-19 being published daily by the world scientific community is impressive (83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93). Since the workshop, as expected for a RNA virus, multiple variants of SARS-CoV-2 have emerged.…”
Section: Looking Back One Year Later: Developments Since the Workhopmentioning
confidence: 99%
“…The possibilities that a time window exists during pregnancy during which ACE2 and TMPRSS2 are coexpressed and that individual variability may influence the strength of this coexpression cannot be excluded. One possible reason for discordant results within the published literature may be the widespread presence of Fc receptors in the human placenta, as these are known to bind antibodies to varying affinities and may therefore lead to nonspecific staining [ 206 , 207 ].…”
Section: Covid-19-related Mcas or Nc-mcas And Possible Consequences F...mentioning
confidence: 99%